Pemanfaatan Aplikasi Canva untuk Pembuatan Media Pembelajaran Kreatif bagi Guru Sekolah Dasar - Tetelepta, Edward Gland; Ginting, Sri Widyanti (Universitas Pattimura, 2025)
Elementary school teachers in Ambon City continue to face challenges in creating creative, technology-based learning media. Limited digital skills and the lack of relevant training are major obstacles in utilizing visual media effectively. This community service activity aimed to enhance teachers’ competence in designing instructional media using Canva, an accessible and user-friendly online graphic design platform. The training was conducted through hands-on workshops, independent practice, and intensive mentoring. Evaluation results indicated a significant improvement across four key indicators: understanding of digital media increased from 45% to 85%, technical skills in using Canva rose from 30% to 80%, media design skills improved from 25% to 78%, and integration of visual media into classroom teaching advanced from 35% to 83%. Additionally, the program encouraged collaboration among teachers and the formation of peer learning communities. The observed transformation demonstrates that teachers have strong potential to adapt and innovate when supported by appropriate training approaches. This activity made a tangible impact on improving the quality of the learning process in elementary schools